WOMEN'S RIGHT FOR RECOGNITION AND PURSUING CAREER IN SAM MENDES' REVOLUTIONARY ROAD (2009): A FEMINIST PERSPECTIVE. - HUTOMO, WESLI ARI SETYO (2011)
The major problem of this study is to reveal how woman gets her right for recognizing and pursuing career are reflected in Sam Mendes' Revolutionary Road. The objective of this study is to analyze the movie based on its structural elements and a feminist approach. This study is a qualitative study. The object of the study is Sam Mendes' Revolutionary Road. The data sources consist of primary and secondary data sources. The primary data source is Revolutionary Road movie itself and the secondary data sources are the other sources relating to the primary data such as the information about the director's biography, websites, and social background of american society at the turn of the twenty first century. The method of the data collection are watching the movie, taking notes the important data, arranging the data based on category of elements of literature review, and the last is making notes of the parts relevant to the analysis. The technique of data analysis is descriptive analysis. This movie contains many facts that are revealed by Sam Mendes which reflect woman's position, woman's role, woman's right, and woman's independence in leading her life as a wife. And there are many forms of subordination, oppression, and exploitation toward woman. The major character, April has a dream to go Paris and gets a better life. But, her dream is hampered by her husband's decision and her pregnancy.